Curating Action: Rethinking Ethnographic Collections and the Role/Place of Performing Arts in the Museum - Bernier, Hélène; Viau-Courville, Mathieu (Museum and Society, 2017)
Dance involves a set of movements that embody social memory. Such forms of intangible heritage have presented emerging challenges for curatorship. This paper draws from the experience of the Musées de la civilisation (Quebec City, Canada) to address ideas of collecting and curating in the performing arts. By presenting the travelling exhibition Rebel Bodies, an international collaborative project that highlights contemporary dance and movement as universal modes of creativity and expression, the paper reflects on the social role of the museum in sustaining creativity within the community as well as on the use of ethnographic material to collectively (through museums and artists) curate the intangible. In treating notions of natural, virtuoso, urban, multi, political, and atypical bodies, this exhibition brings together performers and creative artists as well as industries in the museum setting. Such interplays, it is argued, encourage the sustainable participation of artistic communities/industries and further highlight museums as dynamic loci for the promotion of social change. Keywords: performing arts, intangible cultural heritage, museum, dance, performance, participation, reenactment, artists